2021
DOI: 10.1111/tri.13903
|View full text |Cite
|
Sign up to set email alerts
|

Trends in indications and outcomes of liver transplantation in Canada: A multicenter retrospective study

Abstract: Summary The liver transplantation (LT) landscape is continuously evolving. We sought to evaluate trends in indications for LT in Canada and the impact of primary liver disease on post‐LT outcomes using a national transplant registry. Adult patients who underwent a primary LT between 2000 and 2018 were retrospectively identified in the Canadian Organ Replacement Registry. Outcomes included post‐LT patient and graft survival. A total of 5,722 LTs were identified. The number of LT per year increased from 251 in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…There may be a selection bias as patients with strong opinions on the topic are more likely to respond, particularly those with alcoholic liver disease due to their personal experiences. Compared to a retrospective Canadian study examining aetiologies leading to liver transplantation, our respondents reported a higher rate of NAFLD and a lower rate of hepatocellular carcinoma, but the representation of other liver aetiologies was similar, including ALD [27]. Further, responses of patients with ALD were analysed in comparison to the general study population and found to be largely similar.…”
Section: Discussionmentioning
confidence: 56%
“…There may be a selection bias as patients with strong opinions on the topic are more likely to respond, particularly those with alcoholic liver disease due to their personal experiences. Compared to a retrospective Canadian study examining aetiologies leading to liver transplantation, our respondents reported a higher rate of NAFLD and a lower rate of hepatocellular carcinoma, but the representation of other liver aetiologies was similar, including ALD [27]. Further, responses of patients with ALD were analysed in comparison to the general study population and found to be largely similar.…”
Section: Discussionmentioning
confidence: 56%
“…The rates of obesity in Canadian children and adults continue to rise, which are among the highest globally, and as a consequence, NAFLD has become the most prevalent form of CLD in children and adults (11,12). In parallel, Canadian LT data in adults show a >12% increase in the proportion of LTs performed due to NASH and modelling forecasts a doubling of decompensated cirrhosis with an 80% increase in HCC incidence due to NASH by 2030 (12,13).…”
Section: Non-communicable Cld Trends: Nafld/ Aldmentioning
confidence: 99%
“…In Canada, average alcohol consumption is higher than the global average (8.8 L versus 5.8 L per capita in 2019) and 19.1% of the population reports heavy drinking (14,15). According to a national multicenter registry, ALD-related LTs make up approximately 15% of LTs in Canada (13). ALD and NAFLD are expected to continue battling as the number one and two causes of LT in the future (16).…”
Section: Non-communicable Cld Trends: Nafld/ Aldmentioning
confidence: 99%
“…However, validating studies revealed a poor predictive value of this model, also pointing out the importance of the underlying liver disease (e.g., HCV vs. non-HCV) in different cohorts ( 35 ). In view of the fact that HCV is also displaced by NASH in the LT population ( 36 ), this might become extremely relevant, since many of the models are derived from cohorts with high numbers of patients with viral hepatitis. Other series have focused on an AFP limit of <400 ng/ml and found a low 5-year recurrence rate of 4.9% in patients with a total tumor diameter of <8 cm ( 37 ), or a 4-year recurrence rate of 9.4% in patients with a total tumor volume (TTV) of <115 cm 3 and AFP <400 ng/ml ( 38 ).…”
Section: Can the Role Of The Initial Afp Level Act As A Gatekeeper?mentioning
confidence: 99%